The (In)Coherence of Divine Mercy : A Discourse-Linguistic Analysis of Hosea 12-14 - Turner, Ian B. (Language and Linguistics E-Books Online, Collection 2024., 2024)
How do texts of Scripture make sense or hold together as a unity? This question is especially germane to the Masoretic Text of Hosea, which is often seen as an unintegrated composition by some, or an artful literary whole by others. Such judgmen